2010
DOI: 10.1093/cercor/bhq011
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Connectivity within Human Angular Gyrus and Intraparietal Sulcus: Evidence from Functional and Structural Connectivity

Abstract: The inferior parietal lobule (IPL) of the human brain is a heterogeneous region involved in visuospatial attention, memory, and mathematical cognition. Detailed description of connectivity profiles of subdivisions within the IPL is critical for accurate interpretation of functional neuroimaging studies involving this region. We separately examined functional and structural connectivity of the angular gyrus (AG) and the intraparietal sulcus (IPS) using probabilistic cytoarchitectonic maps. Regions-of-interest (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
397
4
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(452 citation statements)
references
References 100 publications
46
397
4
5
Order By: Relevance
“…50,76 We focused our analysis on hIP3, the most posterior subdivision, based on meta-analysis of previous task-related fMRI studies in the domain of numerical cognition. The meta-analysis was performed using Neurosynth 77 and the search term 'arithmetic'; to increase relevance to our longitudinal developmental study, the search was restricted to studies involving children and adolescents.…”
Section: Ips Seed For Connectivity Analysismentioning
confidence: 99%
“…50,76 We focused our analysis on hIP3, the most posterior subdivision, based on meta-analysis of previous task-related fMRI studies in the domain of numerical cognition. The meta-analysis was performed using Neurosynth 77 and the search term 'arithmetic'; to increase relevance to our longitudinal developmental study, the search was restricted to studies involving children and adolescents.…”
Section: Ips Seed For Connectivity Analysismentioning
confidence: 99%
“…It is likely that such differences in function are underpinned by variations in neural connectivity of the two areas. Recent neuroimaging has revealed that even within the AG there are different patterns of cortical and subcortical connectivity, with the anterior portion more closely associated with a ventral (alerting) attention system (Uddin et al, 2010). The AG also has different connectivity to that of the nearby intraparietal sulcus (Uddin et al, 2010), which was the region targeted by Bolognini et al (2011) in their tDCS study of the flash illusion.…”
Section: Role Of the Parietal Cortex In Audiovisual Integrationmentioning
confidence: 99%
“…Recent neuroimaging has revealed that even within the AG there are different patterns of cortical and subcortical connectivity, with the anterior portion more closely associated with a ventral (alerting) attention system (Uddin et al, 2010). The AG also has different connectivity to that of the nearby intraparietal sulcus (Uddin et al, 2010), which was the region targeted by Bolognini et al (2011) in their tDCS study of the flash illusion. In this context, it was recently reported that patients with acquired brain lesions that display visual extinction have lesions in the AG and superior temporal sulcus, but not the intraparietal sulcus or SMG (Chechlacz et al, 2012;see also, Petrides and Iversen, 1978).…”
Section: Role Of the Parietal Cortex In Audiovisual Integrationmentioning
confidence: 99%
“…Interpretation of PPC functional specialization during episodic retrieval also requires consideration of the growing literature demonstrating that PPC contains a mosaic of subregions, each with unique connectivity, functional properties, and receptor composition (Zilles and Palomero-Gallagher 2001;Grefkes and Fink 2005;Silver and Kastner 2009;Uddin et al 2010;Uncapher et al 2010;Nelson et al 2010;Mars et al 2011;Sestieri et al 2011;Yeo et al 2011;Caspers et al 2012). In light of the debate regarding PPC contributions to attention and memory, a particularly relevant aspect of this recent research has been the discovery and characterization of topographically organized maps of attended visual space in IPS and SPL (for review, see Silver and Kastner 2009).…”
Section: Introductionmentioning
confidence: 99%